2019
DOI: 10.21037/jtd.2019.07.27
|View full text |Cite
|
Sign up to set email alerts
|

Surgical technique modifies the postoperative atrioventricular block rate in sutureless prostheses

Abstract: Background: The main objective was to analyse the impact of the modification of the Perceval S implantation technique on the prevalence of postoperative atrioventricular block, which requires a permanent pacemaker, in our aortic valve replacement series. In addition, we attempted to identify those risk factors that are related to the appearance of this complication. Methods: Five hundred and seventy-two valve replacements were carried out with PERCEVAL S in our centre up to July 2018. Use of modified technique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…For this reason, we place that prosthesis as high as possible, but respecting the implant recommendations. In an in press paper, we reported a patient-prosthesis mismatch (PPM) rate of 2,3%; if we look at the available data on the need for permanent pacemaker in Perceval S series, we find rates ranging from 8 to 23%; after having adopted surgical tricks, the authors found a PPM rate of 4.3% [ 8 ] .…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, we place that prosthesis as high as possible, but respecting the implant recommendations. In an in press paper, we reported a patient-prosthesis mismatch (PPM) rate of 2,3%; if we look at the available data on the need for permanent pacemaker in Perceval S series, we find rates ranging from 8 to 23%; after having adopted surgical tricks, the authors found a PPM rate of 4.3% [ 8 ] .…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we report the feasibility and short‐term safety of LBBAP in patients with conduction disorders following valvular interventions. The main findings of our study are 1 : LBBAP was successfully accomplished in 95% of patients 2 ; LBBAP resulted in significantly narrower QRS duration compared to baseline QRS and was able to normalize activation in LBBB patients as well 3 ; pacing parameters were stable during a mean follow‐up of 8 months; and 4 acute and chronic complication rates were low. To the best of our knowledge, this is the largest series of LBBAP for patients with recent valvular interventions.…”
Section: Discussionmentioning
confidence: 72%
“…As such, atrioventricular block (AVB) is a common complication in patients postvalvular interventions (percutaneous or surgical). The incidence of AVB ranges from 5% to 30% in patients undergoing transcatheter aortic valve replacement (TAVR), 5% to 10% in patients undergoing surgical aortic valve replacement (SAVR), about 25%–30% in patients following tricuspid valve replacement (TVR) and 5%–10% in patients receiving mitral valve repairment or mitral valve replacement (MVR) 2,3 …”
Section: Introductionmentioning
confidence: 99%
“… 10 Also, the absence of preoperative sinus rhythm has been reported as predictors for PPI after valvular surgery. 9 Gonzales Barbeito et al 30 in their series of 519 patients undergoing SAVR with a PERCEVAL S sutureless prosthesis identified disorders of intraventricular conduction and right bundle branch block as predictors for postoperative PPI. In their analysis, atrial fibrillation was not investigated as rhythm disturbances leading to PPI.…”
Section: Discussionmentioning
confidence: 99%